Mathematical modeling for financial analysis of an enterprise: Motivating of not open innovation - Alex Borodin; Irina Mityushina; Elena Streltsova; Andrey Kulikov; Irina Yakovenko; Anzhela Namitulina (Journal of Open Innovation: Technology, Market, and Complexity, 2021)
The article develops economic and mathematical models as a tool for conducting factor financial analysis of the prospects for the development of an industrial enterprise. The functioning of the developed economic and mathematical models is based on the DuPont model, which allows analyzing the dynamics of the company's profitability in the course of two-factor and three-factor financial analysis. The proposed model tools are based on the convergence of deterministic financial analysis methods embedded in the DuPont model and simulation methods that allow analysis under the influence of random factors. The constructed economic and mathematical models for forecasting profitability use the company's retrospective data on its financial condition: the amount of profit, revenue, assets, and equity. The constructed simulation models are implemented in the OMEGA software product and included in the computer technology for predicting the profitability of an industrial enterprise. The architecture of the proposed tools is presented, and the results of simulation experiments performed on models are demonstrated.
Keywords: 650; computer technology; DuPont model; financial analysis; simulation models